2013
DOI: 10.11645/7.2.1852
|View full text |Cite
|
Sign up to set email alerts
|

Faculty perceptions of students' information literacy skills competencies

Abstract: By 'open access' to this literature, we mean its free availability on the public internet, permitting any users to read, download, copy, distribute, print, search, or link to the full texts of these articles, crawl them for indexing, pass them as data to software, or use them for any other lawful purpose, without financial, legal, or technical barriers other than those inseparable from gaining access to the internet itself. The only constraint on reproduction and distribution, and the only role for copyright i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
52
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 29 publications
7
52
0
Order By: Relevance
“…Many studies have found that faculty commonly perceive undergraduate students' IL skills to be below the levels that they would like to see (Bury, 2011;Cannon, 1994;Cope and Sanabria, 2014;DaCosta, 2010;Dubicki, 2013;Duke and Asher, 2012;Gonzales, 2001; Leckie and Fullerton, 1999;Saunders, 2012;Singh, 2005).…”
Section: Faculty Conceptions Of Undergraduates' Information Literacy mentioning
confidence: 99%
“…Many studies have found that faculty commonly perceive undergraduate students' IL skills to be below the levels that they would like to see (Bury, 2011;Cannon, 1994;Cope and Sanabria, 2014;DaCosta, 2010;Dubicki, 2013;Duke and Asher, 2012;Gonzales, 2001; Leckie and Fullerton, 1999;Saunders, 2012;Singh, 2005).…”
Section: Faculty Conceptions Of Undergraduates' Information Literacy mentioning
confidence: 99%
“…This, however, poses the question about skills transfer and what would be a reasonable expectation thereof. In other studies (Dubicki 2013;Saunders 2012), it was shown that students' IL skills mostly improved by year of education and were much-improved by their senior year. The students who formed part of the CPUT study were in their first year and therefore a small improvement could possibly have been expected.…”
Section: Resultsmentioning
confidence: 84%
“…Likewise lecturers! In her research work on the faculty perception of students information literacy skills competencies Dubicki (2013) found out that faculty familiarity with IL concepts was high; faculty are overwhelmingly supportive of IL and are incorporating these skills into learning outcomes for their courses; and there are strong expectations of students" achieving IL skills by graduation, but faculty perceptions are that students fall short of mastering those skills by the end of their programmes.…”
Section: " What We Need In the Knowledge Industries Are People Whomentioning
confidence: 99%
“…The Association of College Research Libraries (ACRL) (2012) has spelt out five information literacy standards, each with its performance indicators and outcomes for assessing the progress of tertiary students studying science and engineering or technology at all levels of higher education towards information literacy. The aim of these standards is to entrench information literacy across all curricula in all tertiary educational programmes in collaboration with the efforts of faculty, librarians and administrators.…”
Section: Introductionmentioning
confidence: 99%